Abstrak Jurnal Litbang Industri Vol. 10 No. 2 Desember Tahun 2020 - Sofyan Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2020)
Abstrak Jurnal Litbang Industri Vol. 10 No. 2 Desember Tahun 2020